2018
DOI: 10.1080/02656736.2018.1469169
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and photobiological basics of water-filtered infrared-A hyperthermia of superficial tumors

Abstract: Thermography-controlled, water-filtered infrared-A (wIRA) is a novel, effective and approved heating technique listed in the ESHO quality assurance guidelines for superficial hyperthermia clinical trials (2017). In order to assess the special features and the potential of wIRA-hyperthermia (wIRA-HT), detailed and updated information about its physical and photobiological background is presented. wIRA allows for (a) application of high irradiances without skin pain and acute grade 2-4 skin toxicities, (b) prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…The computer-based closed feedback system of this device was set to a maximum skin surface temperature between 42. 5 The treatment protocol ( Figure 2) consisted of weekly contact-free, thermography-controlled wIRA-sHT (for 45-60 min), immediately followed by hypofractionated re-RT (4 Gy once per week up to a total dose of 20 Gy), as described in detail earlier [1,25]. Seventeen patients (8%) received a total dose <20 Gy; 7 patients (3%) received a total dose >20 Gy, of them 1 with a modified scheme of 5 × 5 Gy (1 ×/week) split up in 2 × 2.5 Gy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The computer-based closed feedback system of this device was set to a maximum skin surface temperature between 42. 5 The treatment protocol ( Figure 2) consisted of weekly contact-free, thermography-controlled wIRA-sHT (for 45-60 min), immediately followed by hypofractionated re-RT (4 Gy once per week up to a total dose of 20 Gy), as described in detail earlier [1,25]. Seventeen patients (8%) received a total dose <20 Gy; 7 patients (3%) received a total dose >20 Gy, of them 1 with a modified scheme of 5 × 5 Gy (1 ×/week) split up in 2 × 2.5 Gy.…”
Section: Methodsmentioning
confidence: 99%
“…Since 07/2017 all patients were treated with the medical device hydrosun ® -TWH1500 (Hydrosun Medizintechnik, Müllheim, Germany). The computer-based closed feedback system of this device was set to a maximum skin surface temperature between 42.5 and 43 °C, resulting in tissue temperatures >40 °C in a depth of approximately 15 mm, and >39 °C in a depth of approximately 30 mm [25]. Local tumor response (complete response (CR), partial response (PR), no change (NC), progressive disease (PD)) was assessed clinically and-whenever possible-by imaging or biopsy, at the completion of treatment and at follow ups every 6 to 12 weeks in the first year, and every 6 to 12 months thereafter, according to WHO criteria (CR = complete clinical disappearance of all detectable Local tumor response (complete response (CR), partial response (PR), no change (NC), progressive disease (PD)) was assessed clinically and-whenever possible-by imaging or biopsy, at the completion of treatment and at follow ups every 6 to 12 weeks in the first year, and every 6 to 12 months thereafter, according to WHO criteria (CR = complete clinical disappearance of all detectable disease in the treatment fields observed, PR = decrease > 50%, NC = decrease < 50% or increase < 25%, PD = increase > 25%).…”
Section: Methodsmentioning
confidence: 99%
“…It is produced by light from a halogen bulb passing through a water cuvette to abate the irradiances at 970 nm and 1160 nm, and to exclude wavelengths above 1400 nm. Major contributions of visible light (VIS) can be blocked by using an optical longpass filter with a cutoff wavelength at 590 nm [11,12], whereas black filters block VIS (380-780 nm) entirely [13].…”
Section: Wira and Hyperthermiamentioning
confidence: 99%
“…Piazena et al [31] allocated 11 piglets into three intervention groups and irradiated the skin of their thighs with different doses (irradiances) of wIRA. Skin temperatures were measured before, during and after the wIRA irradiation in a 1-min interval in tissue depths of 2,4,7,8,10,12,16, and 20 mm. The temperature measurement revealed (1) significant individual differences between temperature profiles and the thermoregulatory processes, (2) reproducible vertical temperature profiles through the skin layers and subcutis, showing the highest temperature in 4-6 mm depth of the tissue and (3) that the temperature measured at the skin surface is approximately 1-2 K lower than at 4 mm skin depth, allowing an approximate estimation of the temperature reached in deeper layers by temperature measurements at the skin surface [31].…”
Section: Wira and Hyperthermiamentioning
confidence: 99%
“…Recently, Notter et al reported promising data showing the efficacy of wIRA-HT in the treatment of large-sized recurrent breast cancer [23,24]. Piazena et al [6] and Vaupel et al [25] provided related physical and photobiological basics with reference to the ESHO quality assurance guidelines for superficial hyperthermia in oncology [26,27].…”
Section: Introductionmentioning
confidence: 99%